Gold Nanoparticles as Probes for Nano-Raman Spectroscopy: Preliminary Experimental Results and Modeling - V. Le Nader; J.-Y. Mevellec; T. Minea; G. Louarn (International Journal of Optics)
This paper presents an effective Tip-Enhanced Raman Spectrometer (TERS) in backscattering reflection configuration. It combines a tip-probe nanopositioning system with Raman spectroscope. Specific tips were processed by anchoring gold nanoparticles on the apex of tapered optical fibers, prepared by an improved chemical etching method. Hence, it is possible to expose a very small area of the sample (~20 nm2) to the very strong local electromagnetic field generated by the lightning rod effect. This experimental configuration was modelled and optimised using the finite element method, which takes into account electromagnetic effects as well as the plasmon resonance. Finally, TERS measurements on single-wall carbon nanotubes were successfully performed. These results confirm the high Raman scattering enhancement predicted by the modelling, induced by our new nano-Raman device.